The Effect of Preoperative Antiplatelet Therapy on Early Postoperative Rehemorrhage and Outcomes in Patients With Spontaneous Intracranial Hematoma - Yang, Junhua; Liu, Qingyuan; Mo, Shaohua; Wang, Kaiwen; Li, Maogui; Wu, Jun; Jiang, Pengjun; Yang, Shuzhe; Guo, Rui; Yang, Yi; Zhang, Jiaming; Liu, Yang; et al. (Frontiers in Aging Neuroscience, 2021)
Background and Purpose The effect of antiplatelet therapy (APT) on early postoperative rehemorrhage and outcomes of patients with spontaneous intracerebral hemorrhage (ICH) is still unclear. This study is to evaluate the effect of preoperative APT on early postoperative rehemorrhage and outcomes in ICH patients. Methods This was a multicenter cohort study. ICH patients undergoing surgery were divided into APT group and no antiplatelet therapy (nAPT) group according to whether patients received APT or not. Chi-square test, t-test, and Mann–Whitney U test were used to compare the differences in variables, postoperative rehematoma, and outcomes between groups. Multivariate logistics regression analysis was used to correct for confounding variables, which were different in group comparison. Results One hundred fifty ICH patients undergoing surgical treatment were consecutively included in this study. Thirty five (23.33%) people were included in the APT group, while 115 (76.67%) people were included in the nAPT group. The incidence of early postoperative rehemorrhage in the APT group was significantly higher than that in the nAPT group (25.7% VS 10.4%, p = 0.047 < 0.05). After adjustment for age, ischemic stroke history, and ventricular hematoma, preoperative APT had no significant effect on early postoperative rehemorrhage (p = 0.067). There was no statistical difference between the two groups in early poorer outcomes (p = 0.222) at 14 days after surgery. After adjustment for age, ischemic stroke history, and ventricular hematoma, preoperative APT also had no significant effect on early poorer modified Rankin Scale (mRS) (p = 0.072). Conclusion In conclusion, preoperative APT appears to be safe and have no significant effect on early postoperative rehematoma and outcomes in ICH patients.